2017
DOI: 10.3390/nu9060595
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Prognostic Impact between the Child-Pugh Score and Skeletal Muscle Mass for Patients with Liver Cirrhosis

Abstract: Aims: To investigate the influence of skeletal muscle mass index (SMI) as determined by bioimpedance analysis (BIA) (appendicular skeletal muscle mass/(height)2) on survival by comparing the Child-Pugh score in patients with liver cirrhosis (LC, n = 383, average age = 65.2 years). Patients and methods: In terms of comparison of the effects of SMI and other markers on survival, we used time-dependent receiver operating characteristics (ROC) analysis. Results: The average SMI for male was 7.4 cm2/m2 whereas that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Bioelectrical impedance analysis (BIA) has been introduced as a rapid, non-invasive, reproducible, easy to perform, and safe technique for the analysis of body composition including fat, muscle, and water [ 18 ]. In our previous studies using data for BIA, we have demonstrated clinical usefulness of BIA in liver disease patients [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioelectrical impedance analysis (BIA) has been introduced as a rapid, non-invasive, reproducible, easy to perform, and safe technique for the analysis of body composition including fat, muscle, and water [ 18 ]. In our previous studies using data for BIA, we have demonstrated clinical usefulness of BIA in liver disease patients [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…LC, which develops over a long period of time due to the chronic inflammation in the liver, is well accepted to be an end-stage form of chronic liver disease and is accompanied by numerous nutrition disorders [ 8 ]. Of these, protein-energy malnutrition (PEM) is one of the most common complications seen in LC patients, which is associated with high morbidity and mortality in LC patients [ 9 , 10 , 11 , 12 , 13 ]. Thus, appropriate nutritional evaluation is essential for the management of LC patients.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Bioelectrical impedance analysis determined muscle mass was significantly associated with mortality in both men and women. 11 Muscle mass determined by this method was found to be reduced in 36% and 28% of men and women, respectively.…”
Section: Resultsmentioning
confidence: 89%
“…Muscle mass assessed by dual‐energy X‐ray absorptiometry classified 49% of men and 43% of women as having low muscle mass by appendicular SMI, with only men demonstrating a significant survival benefit with increasing appendicular SMI 10 . Bioelectrical impedance analysis determined muscle mass was significantly associated with mortality in both men and women 11 . Muscle mass determined by this method was found to be reduced in 36% and 28% of men and women, respectively.…”
Section: Resultsmentioning
confidence: 93%